The cirrus coupled cloud-radiation experiment: CIRCCREX - Pickering,JC; Fox,C; Murray,JE; Last,A (2015)
We report early results from the Cirrus Coupled Cloud-Radiation Experiment CIRCCREX investigating cirrus through airborne campaigns including radiation measurements (0.3-125μm). Cirrus models and parameterizations used in radiative transfer codes and numerical weather prediction will be tested.